On the anomalous development of the extremely intense positive Arctic Oscillation of the 2019–2020 winter. (27th April 2021) - Juzbašić, A; Kryjov, V N; Ahn, J B
Abstract: Numerous extreme climate anomalies were recorded in the northern extratropics in January–March (JFM) 2020, significantly impacting human lives and ecosystems in the affected areas. Those anomalies were caused by an extreme positive Arctic Oscillation (AO) event, with the JFM 2020 AO index of 2.8 being the highest on the record. However, all well-established autumn precursors pointed towards the following wintertime AO phase being negative. Indeed, a negative AO phase was developing until late December when a sudden shift to the strong positive AO event occurred in the troposphere. The geopotential anomalies associated with positive AO spread into the lower stratosphere, and were steadily enhancing throughout JFM resulting in an extreme positive AO event. We show that the strong positive AO event was a result of the destructive interference of the anomalous planetary waves with climatological ones, which led to wave flattening and enhancement of the polar vortex.